The black tide - Innes, Hammond, 1913- (London : Collins, 1982)
Karen and Trevor have seen too many oil tankers run aground near Land's End, their poisonous cargo turning the waters black and suffocating all natural life for miles around. The Petros Jupiter is the latest devastating wreck, and tired of local committees that have no effect, Karen resolves on more drastic measures. It is left to her husband to unravel the tragedy
Keywords: Adventure -- Fiction